Development of a Small Downdraft Biomass Gasifier for Developing Countries (Journal of Scientific Research, 2010)
Biomass gasification has been receiving increasing attention as a potential renewable energy source for the last few decades. This attempt involved designing, developing and testing a small downdraft biomass gasifier JRB-1 (6-7 kW) at Durham University, UK. The gasifier was built of stainless steel pipes, sheets and other fittings and tested for wood chips and pellets. The composition, moisture content and consumption of biomass feedstock (3.1 kg/hr for wood chips, 2.9 kg/hr for pellets), temperature inside the reaction zone (950-1150 oC), primary air flow rate (0.0015 m3/s) and exit temperature of the producer gas (180-220 oC) was measured. The main constituents of syngas included nitrogen (50-56%), carbon monoxide (19-22%), hydrogen (12-19%), carbon dioxide (10-12%) and a small amount of methane (1-2%). These results were used in Engineering Equation Solver (EES) software to obtain the lower calorific value of syngas (4424-5007 kJ/m3) and cold gas efficiency (62.5-69.4%) of the gasifier, which were found close to the calculated values. Again the thermal efficiency was calculated as 90.1-92.4%. Being comparatively easy to build, downdraft gasifiers like JRB-1 are likely to be the most appropriate technology for developing countries as a source of decentralized power supply and for development in agricultural sector. Keywords:  Biomass gasification; Syngas; Emission; Renewable energy.© 2011 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved.doi:10.3329/jsr.v3i1.5613                J. Sci. Res. 3 (1), 51-64 (2011)